A STUDY REGARDING THE WEIGHT OF THE SPECIFIC MEANS IN THE POLYATHLETIC TRAINING PATTERN FOR 11-14 YEAR OLD CHILDREN (GYMNASIUM, 2009)
The development of psycho-motrical abilities in 11 – 14 year old children is a good motivation formonitoring some of the specific aspects during this age period by analyzing the weight of the main trainingmeans over the annual cycle. The research was achieved through an integrative approach of the training bycorrelating the subjects’ growth and development characteristics with methodical training requirementsspecific to the age group.The progress obtained by the subjects during the second test series after running through the adoptedtraining pattern confirms the correctness of the adopted methodical orientation. Progress of physical traininglevel and physical development corresponds with the stage of growth and development of the subjects.Significant progress was obtained in both mo